Mineralogical and Chemical Properties of Some Acid Sulfate Soils in Malaysia and Their Effects on the Growth Performance of Oil Palm Seedlings (Elaeis Ruineensis, Jacq) - Auxtero, Edgardo Antiga (1990)
Acid sulfate soils are charllcterized by a very low pH and a high aluminium concentration resulting from the chemical and biological oxidation of pyrite upon drainage. These soils have low agricultural potential due to high acidity and poor physical conditions, which adversely affect crop growth. Successful reclamation and management of acid sulfate soils would require an in-depth understanding of the soil's chemical and mineralogical properties. In this study, acid sulfate soils at Pulau Lumut, Kelang were mapped, characterized morphologically and chemically,and classified. Soil solutions were extracted on samples from soil pit,limed and oxidized soils and a pot experiment at the matrix suction of 10 kPa and the activities of the major cations and anions were calculated by Geochem. XRD and TGA were carried out to deter mine the mineralogy of the various soil horizons. The morphological features of the minerals in the soils were studied by TEM and SEM. A controlled pot experiment was conducted to assess the performance of oil palm seedlings grown on acid sulfate soils under freely drained and waterlogged conditions.